2017
DOI: 10.3390/vaccines5020011
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Physicochemical Modification on the Function of Antibodies Induced by Anti-Nicotine Vaccine in Mice

Abstract: Smoking remains one of the major causes of morbidity and mortality worldwide. One approach to assisting smoking cessation is via anti-nicotine vaccines, composed of nicotine-like haptens conjugated to a carrier protein plus adjuvant(s). We have previously shown that the carrier, hapten, linker, hapten load, degree of conjugate aggregation, and presence of adducts can each influence the function (nicotine-binding capacity) of the antibody (Ab) induced. Herein, we extend those findings and show that tertiary str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 22 publications
0
16
0
1
Order By: Relevance
“…46 Instead, drug-conjugate vaccines containing smaller carrier proteins, such as BSA or OVA 39 and TT or CRM 197, 18 can be characterized by MALDI-TOF or other analytical assays. 47 In fact, conjugation conditions are often optimized using BSA and OVA in lieu of larger carrier proteins because it is easier to measure their haptenation ratio. 40,4850…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Instead, drug-conjugate vaccines containing smaller carrier proteins, such as BSA or OVA 39 and TT or CRM 197, 18 can be characterized by MALDI-TOF or other analytical assays. 47 In fact, conjugation conditions are often optimized using BSA and OVA in lieu of larger carrier proteins because it is easier to measure their haptenation ratio. 40,4850…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies tested this hypothesis by immunizing subjects with several batches of nicotine vaccines displaying various degrees of aggregation, and found that the extent of aggregation (and other physical chemical properties of the conjugates) correlated with individual vaccine efficacy against nicotine in both mice and nonhuman primates. 6971…”
Section: Discussionmentioning
confidence: 99%
“…Proses pembentukan spermatozoa sangat sensitif terhadap pengaruh dari luar misalnya yang ditimbulkan oleh asap rokok. Nikotin memiliki partikel yang sangat kecil untuk mengaktifkan sistem imun dan dapat melewati sawar darah otak (Thorn et al, 2017).…”
Section: ¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯unclassified
“…It would be indicated for the following groups of subjects: (a) heavy smokers who have made multiple unsuccessful attempts to quit using different methods; (b) patients who are highly motivated to quit; and (c) patients who have positive attitudes toward vaccines 20 . Modifications designed to improve serum antibody affinity are being tested and may improve the performance of future clinical candidate vaccines [21][22][23] .…”
Section: Vaccinesmentioning
confidence: 99%